Competência Social de crianças autistas de alto funcionamento: Teoria da Mente Aplicada e Pragmática - Azevedo, Gyovanna Mazzocco Machado (2023)
Deficits in Theory of Mind and Pragmatics have already had their mediating role related to autism, constituting crucial elements in psychological studies on the disorder. However, understanding the social competence of children with high-functioning autism is still a challenge for researchers. In this sense, the aim of this study was to investigate how Applied Theory of Mind and Pragmatics are associated with the symptoms and social competence of children with High Functioning Autism. For this purpose, a descriptive study of multiple cases was outlined, in which three children with High Functioning Autism and their respective caregivers answered the Theory of Mind Inventory 2 (adapted), the ABFW Child Language Test (Pragmatics - Part D), the Child Behavior Checklist for Ages 6-18 (CBCL 6- 18), and the Verbal Behavior Milestone Assessment and Grading Program (Social Behavior and Social Play Milestones and Classroom Routines and Group Skills levels 2 and 3). The data provided by the application of these instruments integrated the corpus for case descriptions, which were analyzed through an analytical strategy using the cross synthesis of cases. The results point to a lowering of pragmatic skills, applied knowledge of Theory of Mind and social competence. It is argued that, although the participants present lowering of skills, their profiles are heterogeneous. The relevance of Theory of Mind and pragmatics skills in understanding the social competence of high-functioning autistic children is concluded, and future studies should consider the dimensions involved in these skills and determine the direction of the causal relationship established between the variables.